2018
DOI: 10.1634/theoncologist.2018-0128
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Nivolumab-Induced Bullous Pemphigoid: Review of Dermatologic Toxicity Associated with Programmed Cell Death Protein-1/Programmed Death Ligand-1 Inhibitors and Recommendations for Diagnosis and Management

Abstract: Bullous pemphigoid is an autoimmune subepidermal blistering disease characterized by the development of tense bullae and is most frequently seen in the elderly. PD‐1/PD‐L1‐induced bullous pemphigoid (BP) has emerged as a potentially serious dermatologic toxicity. This article reports a case of a 72‐year‐old woman who developed BP shortly after initiating treatment with the PD‐1 inhibitor nivolumab for metastatic non‐small cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 87 publications
(129 reference statements)
1
59
0
Order By: Relevance
“…Overall, our data (a) confirmed the variegate pattern of cutaneous toxicity , including nonspecific manifestations such as rash maculopapular and pruritus, as well as serious irAEs and SCARs, thus making a timely consultation with dermatologist pivotal to minimize unnecessary drug interruption ; (b) found a differential reporting between anti‐PD1/PDL1 drugs (psoriasis, dermatitis psoriasiform, pemphigoid, and cutaneous sarcoidosis) and anti‐CTLA4 medications (acute febrile neutrophilic dermatosis and erythema nodosum) ; and (c) recorded a high proportion of death in young adults with SCARs, especially TEN (83% in adults aged 40–49), with a delayed latency as compared with recently published data on anticancer drugs (mean 46 vs. 18 days ), in keeping with immune‐related basis. This conflicts with the algorithm of drug causality for epidermal necrolysis (ALDEN), which was validated on heterogeneous drugs and suggested that late events are unlikely to be drug related ): we invite clinicians to submit complete high‐quality reports, as recommended by the Side Effect Reporting in Immuno‐Oncology (SERIO) working group .…”
Section: Resultssupporting
confidence: 75%
“…Overall, our data (a) confirmed the variegate pattern of cutaneous toxicity , including nonspecific manifestations such as rash maculopapular and pruritus, as well as serious irAEs and SCARs, thus making a timely consultation with dermatologist pivotal to minimize unnecessary drug interruption ; (b) found a differential reporting between anti‐PD1/PDL1 drugs (psoriasis, dermatitis psoriasiform, pemphigoid, and cutaneous sarcoidosis) and anti‐CTLA4 medications (acute febrile neutrophilic dermatosis and erythema nodosum) ; and (c) recorded a high proportion of death in young adults with SCARs, especially TEN (83% in adults aged 40–49), with a delayed latency as compared with recently published data on anticancer drugs (mean 46 vs. 18 days ), in keeping with immune‐related basis. This conflicts with the algorithm of drug causality for epidermal necrolysis (ALDEN), which was validated on heterogeneous drugs and suggested that late events are unlikely to be drug related ): we invite clinicians to submit complete high‐quality reports, as recommended by the Side Effect Reporting in Immuno‐Oncology (SERIO) working group .…”
Section: Resultssupporting
confidence: 75%
“…Besides melanoma, one case of lichen planus pemphigoides [140] and one of bullous pemphigoid [141] have been reported for patients treated with check-point inhibitor immunotherapy for NSCLC. Besides melanoma, one case of lichen planus pemphigoides [140] and one of bullous pemphigoid [141] have been reported for patients treated with check-point inhibitor immunotherapy for NSCLC.…”
Section: Additional Autoimmune Skin Diseases In Melanoma Patients Trementioning
confidence: 99%
“…The reader should bear in mind that expert opinion is the sole evidence for these agents in immunotherapy‐related cases and not currently included in any guidelines. A recent case also demonstrated the effective use of oral minocycline and oral niacinamide as adjunctive therapies in a case of bullous dermatitis …”
Section: Discussionmentioning
confidence: 99%